Transmission power adaptations for data collision avoidance in wireless ad hoc networks. (1st March 2013) - Chang, Chau–Chieh; Chen, Yen–Da; Liao, Wen–Hwa; Shih, Kuei–Ping
The paper proposes a fragmentation–based MAC protocol with power control, named F–RCRC MAC protocol, for wireless ad hoc networks to avoid the Large Interference Range Collision (LIRC) problem, which is a kind of hidden terminal problem. F–RCRC designs a new interframe space, called FIFS, to reduce the overhead caused by the fragmentation scheme. Taking advantage of fragmentation, the design of FIFS can effectively avoid the hidden STAs from interfering with the receiver's reception. F–RCRC can reduce the energy consumption and increase the spatial reuse due to the controlled transmission power. Simulation results show that F–RCRC performs much better than the related work in terms of network throughput as well as energy efficiency.